IMPROVING STUDENTS’ WRITING SKILLS IN PERSONAL LETTER BY MASTERING STRUCTURE OF THE TEXT - Mariani; Kurniati, Tien; Mashuri, Mashuri (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aims to investigate the effectiveness of mastering the structure of the text to improve students’ writing skills in personal letters by mastering the structure of the text at second-year students of MA. Alkhairaat Biromaru. This is a classroom action research. The object of this research is the second-year students of MA. Alkhairaat Biromaru consisting 21 students. This research was conducted in two cycles. The researchers used tests, observation for teachers and students, and LKS (project paper activity) to collect the data. The test research results show that the students’ writing skills in personal letters by mastering the structure of the text can be improved from the first cycle to the second one. The students’ test results can prove it in the first cycle, the classical competence percentage is 47,61%, and the classical absorption presentation is 60,95% can be improved to 85,71% for classical competence presentation and 83,33% for classical absorption presentation in cycle II. It means that the students’ writing skills in personal letters can be improved by mastering the structure of the text.